Composer avec l’expectation actorielle dans la relation chercheur-acteurs - Julien de Miribel (Éducation et Socialisation)
This research paper studies the relationship between the researcher and the actors of the field regarding actors’ expectation and its effect on the research process. This article results of a PhD research led through a CIFRE research and training agreement programme and favouring a participant observation. It states a self-analysis of the researcher’s posture while he has to deal with an expectation expressed by some actors of the field, psychiatric nurse-tutors. The reaction to these expectations led him to take part in working days bringing together these tutors and to give them back some research data concerning them. He thus identifies a hidden function which constitutes a resource for the activity of tutors, both in the context of tutoring and in the care services. If this constructive aspect is underlined, this reaction to the actors’ expectation however calls for a questioning of its subjective and institutional bases.